Psychoeducational Program for the Family Member Caregivers of People with Dementia to Reduce Perceived Burden and Increase Patient's Quality of Life: A Randomized Controlled Trial - Nadia M. Tawfik; Noha A. Sabry; Hatem Darwish; Maha Mowafy; Saeed S.A. Soliman (SAGE Publishing, 2021)
Background: Dementia is one of the world's greatest public health issues. Most people with dementia receive home care, and family members are vulnerable to feeling burdened and depressed that reinforces the need for caregiver-driven services to mitigate these negative effects. Objective: The purpose of this research was to evaluate the effect of the psychoeducational program on burden and quality of life of family caregivers for people with dementia. Methods: This randomized controlled trial ( RCT) was conducted on 60 family caregivers. Participants were randomly assigned to receive either the 8-session psychoeducational program (study group) or routine care only (control group). The demographic data of the caregivers and their patients, the burden of caregivers using Zarit Burden Interview (ZBI), and the quality of life of the patients using Quality of Life in Alzheimer Disease (QoL-AD) questionnaire were measured before and after the psychoeducational program and compared between the study group and the control group. Results: The results revealed that 80% of the family caregivers were female and 42% were daughters. The mean ± SD of the baseline burden was 61 ± 13.7 and 60.9 ± 10 in the study and the control group, respectively. ZBI burden score in the study group demonstrated a significant drop after the psychoeducational program compared to the control group. Logistic regression analysis showed that caregivers who received the psychoeducational program have OR (95% CI) of 14 (3.1-67.8) compared to those who did not receive the psychoeducational program. Conclusions: Psychoeducational program is effective in reducing the family caregivers' perceived burden. These findings need to be considered in developing comprehensive dementia care programs to well increase the strategies that help caregivers to deal with their patients.